REVITALISASI KONSTITUSI DALAM IDEOLOGI TERBUKA PANCASILA - Kertopati, Ton (Universitas Prof. Dr. Moestopo (Beragama), 2007)
We have been asked to think about a convention that will write a new constitution for the Indonesian Republic. What our reaction?We were surprised of idea of a new constitution? Why? Do we assume the present constitution/ the first and oldest one w!II remain in force forever?Our present constitution provides several methods of amendment. Why didn't the founding fathers include on amendment clause?How did we react to the suggestion that we were to participate in the new convention?Of course, existence of a certain particular constitutional features are desirable for the nation actual constitutions can provide inspiration but cannot tell us what is desirable.To reach conclusions about desirability, we must employ principles of evaluation.These are serious doubts that a new constitution should be helcl obviously no convention should be called, it can be expected to write a bitter constitution than we already have. Our constitution is thus not just a set of legal rules, It is also a paradigm.A paradigm is an overall view of things in terms of which particular experiences con be understoodMost of the young Indonesian modern generation now days encourages decision makers to egotism.Pragmation appears lo give possible scope for the exercise of common sense new elements in Indonesian life. To be pragmatic thus implies the opposite of being dogmatic theoretical or ideological.There is a widespread belief-Constitution means limited government.To be pragmatic as a dogma or ideological Pancasila appears to give maximum scope the exercise of common sense.As an open ideology Pancasila is better at least lo stumble around, than to go in the wrong direction. Not such as the Nazis exterminated the Jews, six. million of them/ in pursuit the dogma or ideology of